Implementation of higher order thinking skills in teaching of science: a case study in Malaysia - Sulaiman, Tajularipin; Muniyan, Vickneswary; Madhvan, Diwiyah; Hasan, Raidah; Abdul Rahim, Suzieleez Syrene (Malaysia Association of Research and Education for Educators, 2017)
Higher order thinking skills (HOTS) is a skill that should be present in every teaching. Teaching science particularly require teachers to be skillful in planning learning activities that can inculcate thinking skills among students. This study aims to explore the perceptions of science teachers in the implementation higher order thinking skills in teaching science. This is a qualitative case study involving three science teachers who teaches in government school, private school and private tuition center respectively. Data were collected through interviews only. Data were then categorized to form themes for the study. The focus of the study was teachers’ perspective, towards HOTS, its application, assessment of HOTS and the constraints. The results show that the teachers are aware and they are applying HOTS in their teaching. However, they believe they are hindered by some constraints. Therefore this study concluded that knowledge and competence are crucial to ensure quality the implementation of HOTS.